Penguatan Literasi Keuangan Islam untuk Ketahanan Keluarga Ibu-ibu Majlis Taklim Tasikmalaya - Sudirman, Iman Fauzi; Assalam, Abdu; Lestari, Deva; Takiyah, Nida (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Low Islamic financial literacy and weak household financial management remain critical challenges among women members of Majlis Taklim, despite their strategic role in family financial decision making. This community service aims to develop and implement a community-based model of Islamic financial literacy integrated with Sufism values to strengthen sakinah family economic resilience. Using a Participatory Action Research (PAR) approach, the program engaged women from Majlis Taklim in Tasikmalaya through baseline assessment, participatory training, mentoring, and evaluation. The intervention integrated practical financial skills with internalized Sufism values as behavioral change mechanisms. The results show a significant increase in Islamic financial literacy, budgeting practices, financial record-keeping, emergency savings awareness, and the use of Islamic financial products, accompanied by improved financial attitudes characterized by self-control and orientation toward barakah. This program demonstrates that Majlis Taklim can function as an effective institutional platform for sustainable and replicable Islamic financial literacy empowerment at the community level.